Book review: Bourn, Douglas. 2015: The Theory and Practice of Development Education: A Pedagogy for Global Social Justice. (April 2016) - Dalby, Tom Pablo
Bourn, Douglas. 2015: The Theory and Practice of Development Education: A Pedagogy for Global Social Justice . New York: Routledge. 222 pp. £95.00 clothbound, £29.99 paperback, £23.51 e-book. ISBN: 978-1-138-80476-0 (clothbound). ISBN: 978-1-138-80477-7 (paperback). ISBN: 978-1-315-75273-0 (e-book).